A seven‐long noncoding RNA signature predicts relapse in patients with early‐stage lung adenocarcinoma. Issue 9 (3rd May 2019) - Zhou, Huihui; Zhang, Hongwei; Chen, Juan; Cao, Jiangbo; Liu, Lin; Guo, Cheng; Huang, Ge; Zeng, Danli
Abstract: Background: Long noncoding RNA (lncRNA) has been increasingly reported to play crucial roles in cancer development. In this study, we aim to develop a lncRNA‐based signature to predict the relapse of early‐stage (stage I‐II) lung adenocarcinoma (LUAD). Methods: With a lncRNA‐mining strategy, lncRNA expression profiles of three LUAD cohorts were obtained from the Gene Expression Omnibus database. A risk score model was established based on the lncRNAs expression from training set (GSE31210, n = 204) and further validated in two independent testing sets (GSE50081, n = 124; and GSE30219, n = 84). The potential signaling pathways modulated by the prognostic lncRNAs were explored using bioinformatics analysis. Results: In the training set, seven lncRNAs were identified to be significantly correlated with the relapse‐free survival (RFS) of early‐stage LUAD, and were then aggregated to form a seven‐lncRNA prognostic signature to classify patients into high‐risk and low‐risk groups. Individuals of training set in the high‐risk group exhibited a poorer RFS than those in the low‐risk group (HR: 7.574, 95% CI: 4.165‐13.775; P  < 0.001). The similar prognostic powers of the seven‐lncRNA signature were also achieved in the two independent testing sets and in stratified analysis. Multivariate Cox regression indicated that the prognostic value of seven‐lncRNA signature was independent of other clinical features. Functional enrichment analysis found that the seven‐lncRNA signature may be involved in biological pathways such as cell cycle, DNA replication, and p53 signaling pathway. Conclusion: Our results indicate that the seven‐lncRNA signature may be an innovative biomarker to predict the relapse of early‐stage LUAD. Abstract : In this study, we identified seven lncRNAs that were significantly associated with the relapse of early‐stage lung adenocarcinoma. The seven‐lncRNA signature showed good performance in relapse prediction of early‐stage lung adenocarcinoma.